2023
DOI: 10.1002/pen.26499
|View full text |Cite
|
Sign up to set email alerts
|

A novel green synthesis approach for shape memory polymer nanocomposites decorated with silver nanoparticles

Sibel Selçuk Pekdemir,
Burcu Karagulle,
Mustafa Ersin Pekdemir
et al.

Abstract: A new, low‐cost, and direct green synthesis strategy was developed for the preparation of polymer composites composed of silver nanoparticles (AgNPs) decorated on a shape memory polymer blend using Rubus caesius L. leaves. X‐ray powder diffraction, ultraviolet‐visible spectroscopy (UV–vis), scanning electron microscopy, and energy dispersive X‐ray spectroscopy (EDS) elemental composition were applied to characterize the crystal size, morphology, and elemental composition of Ag‐NPs. UV–vis spectra detected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The sharp and strong signal seen at 1753 cm −1 is attributed to the characteristic C=O stretching vibrations of PLA, and the signal at 1722 cm −1 is attributed to the characteristic C=O stretching vibrations of PHA [23] . Asymmetric −CH bending appeared at 1452 cm −1 , and symmetrical −CH bending appeared at 1380 cm −1 [24] . The peaks at 1181 cm −1 and 1089 cm −1 are asymmetric and symmetric stretching of C−O−C stretching vibrations, respectively [25] .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The sharp and strong signal seen at 1753 cm −1 is attributed to the characteristic C=O stretching vibrations of PLA, and the signal at 1722 cm −1 is attributed to the characteristic C=O stretching vibrations of PHA [23] . Asymmetric −CH bending appeared at 1452 cm −1 , and symmetrical −CH bending appeared at 1380 cm −1 [24] . The peaks at 1181 cm −1 and 1089 cm −1 are asymmetric and symmetric stretching of C−O−C stretching vibrations, respectively [25] .…”
Section: Resultsmentioning
confidence: 95%
“…[23] Asymmetric À CH bending appeared at 1452 cm À 1 , and symmetrical À CH bending appeared at 1380 cm À 1 . [24] The peaks at 1181 cm À 1 and 1089 cm À 1 are asymmetric and symmetric stretching of CÀ OÀ C stretching vibrations, respectively. [25] Although there was no visible change in the signals of PLA and PHA as the NiMnSb alloy was added, it was observed that the characteristic À C=O stretching signal intensity decreased with increasing percentage of the alloy.…”
Section: Atr-ir Analysismentioning
confidence: 99%